Hybrid Control System for Greater Resilience Using Multiple Isolation and Building Connection - Taniguchi, Masaki; Fujita, Kohei; Tsuji, Masaaki; Takewaki, Izuru (Frontiers in Built Environment, 2016)
An innovative hybrid control building system of multiple isolation and connection is proposed and investigated using both time-history and input energy responses for various types of ground motions together with transfer functions. It is concerned that the seismic displacement response at the base-isolation layer of the existing base-isolated buildings may extremely increase under long-period and long-duration ground motions which are getting great attention recently. In order to enhance the seismic performance of those base-isolated buildings, a novel hybrid system of multiple isolation and building-connection is proposed and compared with other structural systems such as an independent multiple isolation system, a hybrid system of base-isolation and building-connection. Furthermore, the robustness of seismic responses of the proposed hybrid system for various types of ground motion is discussed through the comparison of various structural systems including non-hybrid systems. Finally the optimal connection damper location is investigated using a sensitivity-type optimization approach.